Knowledge Acts in Modern China : Ideas, Institutions, and Identities - Yeh, Wen-Hsin 1950-; Yeh, Wen-Hsin 1950-; U, Eddy; U, Eddy; Culp, Robert Joseph 1966-; Culp, Robert Joseph 1966- (Book collections on Project MUSE., 2016)
"This book examines as interrelated processes the reception of foreign systems of thought, the construction of modern academic and professional disciplines, and the emergence of new social identities in twentieth-century China after the fall of the imperial state and with the rise of political parties and mass nationalism."